APLIKASI ASAP CAIR BERBASIS KESAMBI DENGAN KONSENTRASI BERBEDA TERHADAP PERKECAMBAHAN JAGUNG PUTIH LOKAL TIMOR - Stormy Vertygo; Belni S Naimasus; Bernadeta N Go'o; Rita L Mate; Basry Yadi Tang (Partner, 2022)
The province of East Nusa Tenggara (NTT) has several local maize varieties that are proven to be more resistant to pest than hybrid varieties. Unfortunately, the local varieties have very low growth and development that in turn, hinder its productivity. Research on the effect of kusum tree (Schleichera oleosa) derived liquid smoke on the germination and growth of white local maize variety has been conducted. Treatments used different concentration as follows: P0: 0% of liquid smoke (control), P1: 10%, P2: 20%, P3: 30% and P4: 40%. Results showed no significant effect on germination percentage (GT) and mean germination time (MGT). However, it has significant effect on the number of leaves/sprout where the P1 andP2 treatment gave the best result. This could serve as an alternative method for farmers in cultivating their maize crops for a better productivity yield, especially for use as livestock feed.  Keywords: White maize, Liquid smoke, Kusum tree, Germination, Timor local variety.